Are Dual-System Offenders Different? An Examination of Prevalence and Specialization in Criminal Offending and Child Maltreatment Perpetration. (August 2021) - Craig, Jessica M.; Stewart, Anna; Hurren, Emily
Although most theoretical and policy approaches treat criminal behavior and child maltreatment as different issues, we examine the prevalence of those involved in both the criminal justice system and child protective services as perpetrators, assessing how several criminal career characteristics differ between dual-system and single-system offenders. Using longitudinal cohort data from the Queensland Cross-Sector Research Collaboration (QCRC), we found that while dual-system-involved offenders made up only 4% of the population, their proportion was much higher among those with a delinquent history, especially among females (males = 21%, females = 38%). Those involved with both systems were more serious offenders and child maltreatment perpetrators with respect to the number and versatility of system contacts. These findings suggest involvement in both the criminal justice and child welfare systems are part of an underlying vulnerability or predisposition toward antisocial behavior and represent an important overlap of service delivery that must be managed effectively.